Effect of Nosema bombycis infected in grown silkworm stage to causing pebrine-contaminated noth - SHI Lian-gen; ZHONG Bai-xiong (浙江大学学报. 农业与生命科学版, 2001)
The effect of Nosema bombycis infected in grown silkworm stage and pebrine-contaminated noth diagnosed by microscope was investigated by peroral microinjection. The diagnostic times of pebrine disease were earlier with the larger injected dosages of N. bombycis. Injecting 32-64 spores per larvae in grown silkworm stage were the minimum dosages that cause pebrine-contaminated noth diagnosed by microscope. The minimum dosages differ in injected stages. These results have practical value to the control of pebrine disease of the silkworm in silkworm eggs production at present.